Modified Limberg Flap for Pilonidal Sinus - Prabin Bikram Thapa; DK Maharjan; R Ghimire; SK Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Pilonidal sinus disease is a common condition usually seen in young adults. Although several methods of treatment have been described, but all have been associated with high recurrence rates. This study was carried out to evaluate the advantages and results of rhomboid excision and Limberg flap reconstruction in the management of pilonidal sinus disease.